2019
DOI: 10.1002/ccr3.2400
|View full text |Cite
|
Sign up to set email alerts
|

Multiple management strategies to prolong gestational period after radical trachelectomy

Abstract: Preterm premature rupture of membranes and massive genital bleeding in the second trimester are serious obstetrical problems in pregnancy after trachelectomy. We had managed a twin post‐trachelectomy pregnancy by multiple strategies, and two healthy infants were delivered at 32+5 weeks, although the optimum management for such patients is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We as well as Speiser et al administered Metronidazole vaginal tablets for the treatment of BV during pregnancy [19]. Ito et al reported the usefulness of oral probiotics to reduce the occurrence of BV and the following pPROM for a patient after RT [20].…”
Section: Discussionmentioning
confidence: 92%
“…We as well as Speiser et al administered Metronidazole vaginal tablets for the treatment of BV during pregnancy [19]. Ito et al reported the usefulness of oral probiotics to reduce the occurrence of BV and the following pPROM for a patient after RT [20].…”
Section: Discussionmentioning
confidence: 92%
“…Ito et al reported dichorionicdiamniotic twins after RT with multiple abnormal bleedings during pregnancy. They controlled abnormal bleeding by compression using dry gauze [50]. In our experience, hemostasis is often achieved by compression; however, in one case where hemostasis was difficult to achieve, we used an argon laser to stop the bleeding.…”
Section: Varices At the Site Of Uterovaginal Anastomosismentioning
confidence: 98%
“…Among the pregnant women after RT, there are reports of ten women pregnant with twins published previously (Table 1) [10,40,50,[57][58][59][60][61][62]. Since perinatal outcomes were not reported in detail, there was a dearth of information on managing a twin pregnancy in women after RT.…”
Section: Twin Pregnancymentioning
confidence: 99%